Pre-Surgical Orthopedic Treatment Using Hotz Plate: An Update - SANJIDA HAQUE,; MOHAMMAD KHURSHEED ALAM, (International Journal of Pharma and Bio Sciences, 2015)
Throughout infancy, several difficulties like feeding, deglutition, articulation with aesthetic appearance are faced by cleft lip and palate (CLP) patients. Hotz plate is a passive pre surgical neonatal maxillary orthopedic appliance used in CLP patient after birth which facilitates not only in sucking and feeding but also exploit for treatment purpose. The prime purpose of this study was to evaluate the benefit of Hotz plate in patients with CLP and also to assess the effect of Hotz plate on enhancement of treatment outcome. A literature survey was executed on a Hotz plate in CLP patients by following terms: ‘passive pre surgical orthopedic appliances and/or ‘Hotz plate’ and ‘cleft lip and palate’. The electronic database including Medline-PUBMED, Science Direct, and ISI Web of Knowledge were searched from 1990 to 2014, and 10,311 relevant articles were found. Of these, we identified 41 articles including original articles and literature reviews. Even though the results differ from case to case because of anatomic and functional variability, this orthopedic appliance produced some changes in CLP patients. This update can generate better knowledge regarding the uses, advantages, and treatment effectiveness of Hotz plate. It can facilitate assessment and provide the momentum needed for a sustained upgrade in the standards of care for CLP in daily orthodontics.